Blood Pressure Level Is Associated With Changes in Plasma Aβ1 –40 and Aβ1–42 Levels: A Cross-sectional Study Conducted in the Suburbs of Xi’an, China - She, Meilin; Shang, Suhang; Hu, Ningwei; Chen, Chen; Dang, Liangjun; Gao, Ling; Wei, Shan; Huo, Kang; Wang, Jingyi; Wang, Jin; Qu, Qiumin (Frontiers in Aging Neuroscience, 2021)
Objectives: Amyloid-β (Aβ) deposition in the brain is the hallmark of Alzheimer’s disease (AD) pathology. Hypertension is a risk factor for AD, but the effects of hypertension on Aβ deposition is not fully determined. Considering peripheral Aβ closely relate to Aβ deposition in the brain, we investigated the relationships between blood pressure (BP) level and plasma Aβ concentrations. Methods: 1069 participants (age above 45) from a village in the suburbs of Xi'an, China were enrolled. Questionnaires and validated Chinese version of the Mini-Mental State Examination were used to collect information about vascular risk factors and assess cognition function. The apolipoprotein E (ApoE) genotype was detected using PCR and sequencing. Plasma Aβ levels were measured using ELISA. The associations between BP and plasma Aβ levels were analysed by using multivariate linear regression. Results: Plasma Aβ1-40 level was higher in high BP group than that in normal BP group (53.34±8.50 pg/ml vs. 51.98±8.96 pg/ml, P=0.013), in high SBP group than that in normal SBP group (53.68±8.69 pg/ml vs. 51.88±8.80 pg/ml, P=0.001) and in high MABP group than that in normal MABP group (54.05±8.78 pg/ml vs. 52.04±8.75 pg/ml, P=0.001). After controlling for the confounding factors, SBP (b=0.078, P<0.001), DBP (b=0.090, P=0.008) and MABP (b=0.104, P<0.001) correlated with plasma Aβ1-40 level positively in ApoE ε4 non-carriers, but not ApoE ε4 carriers. Conclusions: Elevated BP levels were associated with increased plasma Aβ1-40 levels in middle-aged and elderly ApoE ε4 non-carriers.